Hybrid Automaton Control of Three Phase Reduced Switch Shunt Active Power Filter Connected Photovoltaic System. Issue 2 (2020) - Hekss, Z.; Abouloifa, A.; Janik, J.M.; Lachkar, I.; Echalih, S.; Chaoui, F.Z.; Giri, F.
Abstract: In this paper, a new controller design method based on hybrid automaton approach is proposed to solve the problem of controlling a three-phase reduced switch shunt active power filter (SAPF) connected to photovoltaic system. The control objective is two-fold: (i) ensuring a satisfactory power factor correction (PFC) by compensating the harmonic and reactive currents absorbed by the nonlinear load; (ii) regulating the voltage in the output of the photovoltaic panels to track a reference provided by the MPPT block in order to guarantee the power exchange between the photovoltaic source and three-phase electrical power grid. The considered control objectives are dealt with using a new two-loop cascaded controller. The hybrid automaton approach is applied in the inner loop, which ensures the operation modes of switching design in order to ensure a unity power factor. A proportional-integral (PI) regulator is used in the outer-loop to ensure the tight regulation of the voltage across the photovoltaic panels with a well-known P&O algorithm (MPPT). Finally, it is demonstrated through simulation results under Matlab/Simulink SimPowerSystems environment that the proposed automaton model and its controller can achieve the desired objectives.